Multifunctional Children Clothing Design Process Based on the Eco-Fashion Design Model - Siti Shukhaila Shaharuddin; Marzie Hatef Jalil (Journal of Visual Art and Design, 2021)
The purpose of this study was to develop the design of multifunctional children’s clothing that supports sustainability goals. This paper proposes multifunctional clothing that can be recycled and decomposed at the end of the clothing’s lifespan. In particular, the Eco-fashion design model was adopted in this project. After analyzing fashion consumption and problems in children’s product design, four items of multifunctional children’s clothing were developed. Multifunctional children’s clothing design focuses on material selection, zero-waste techniques, design for disassembly and children’s health. Thus, the minimization of material diversity as well as the application of zero-waste design techniques and multifunctional design guidelines for children’s clothing design can be implemented towards sustainability in order to preserve the environment by selecting recyclable materials, promoting profit and human health concerning multifunctional purposes and international standards for children’s clothing design. The ﬁndings can be used in various apparel products to help mitigate problems related to environmental pollution and resource depletion in the apparel industry.